Studies of selected aspects of business in Europe - Cranfield Management Development Programme no. 7. (College of Aeronautics, 1968)
Preface The Cranfield Management Development Programme is an intensive ten week course for middle management aged 28 - 45. The courses which are held twice yearly started in 1964; the seventh of these, M.D.P.7, was held from October - December 1967. The members of the course are drawn from a variety of businesses and have previous experience in one or more of the main fields of business activity, e.g. general management, marketing, production, finance. As part of the course two weeks are devoted to studying business conditions on the continent of Europe. For this tour the members are formed into small groups who study particular projects. Throughout the visits the emphasis is on discussion with Senior Executives. The specific objectives of the European Tour are:- 1. To use this exposure to a new environment to effect some measure of re-evaluation of their past business experience in the United Kingdom. 2. To acquaint members with business problems in different European environments and to Provide an opportunity to discuss business Problems with European managers. To study problems that confront British companies who do business in or with European countries. M.D.P. 7 were in Europe from 12th - 24th November 1967 during which Period the following cities were visited; Gothenburg, Copenhagen, Hamburg, Rotterdam and Brussels. In each city discussions were arranged -with a representative cross-section of the business community. These included British Embassy Staff, British Chambers of Commerce, Local Bankers, Industrial Companies, Advertising Agents, Trade Union Officials, Management Consultants, British Subsidiaries and the E.E.C. Commission. This report is split into sections representing the work of the project groups. The time available was not sufficient for a study in depth of any of the chosen subjects. Nevertheless the large number of interviews and frank discussions with British and foreign businessmen enabled the writers to gain an insight into many aspects of European business. The report must necessarily concern itself largely with opinions - those of the writers and the persons interviewed. The College would like to express its appreciation of the co-operation and frank answers to searching questions received from all the businessmen, trade unionists and others we had the pleasure of meeting during the tour. We would like to give particular thanks to those who entertained the course members. The success of the tour owes a very great deal to the hard work done on our behalf by British officials. In particular thanks are due to the Foreign Office (Economic Section), Board of Trade (Export Services Branch) and the Embassies or Consulates in the cities visited.